Biomineralization of calcium carbonate polymorphs by the bacterial strains isolated from calcareous sites - Dhami, N.; Reddy, M.; Mukherjee, Abhijit (Han'gug Mi'saengmul Saengmyeong Gong Haghoe, 2013)
Microbially induced calcium carbonate precipitation (MICCP) is a naturally occurring biological process that has various applications in remediation and restoration of a range of building materials. In the present investigation, five ureolytic bacterial isolates capable of inducing calcium carbonate precipitation were isolated from calcareous soils on the basis of production of urease, carbonic anhydrase, extrapolymeric substances, and biofilm. Bacterial isolates were identified as Bacillus megaterium, B. cereus, B. thuringiensis, B. subtilis, and Lysinibacillus fusiformis based on 16S rRNA analysis. The calcium carbonate polymorphs produced by various bacterial isolates were analyzed by scanning electron microscopy, confocal laser scanning microscopy, X ray diffraction, and Fourier transmission infra red spectroscopy. A strainspecific precipitation of calcium carbonate forms was observed from different bacterial isolates. Based on the type of polymorph precipitated, the technology of MICCP can be applied for remediation of various building materials.